Mall walking circuit: elevated walkway to improve walkability in Kuala Lumpur / Andi Zhang ... [et al.] - Zhang, Andi; -, Raja Norashekin; Zubir, Syed Sobri; Amirrol, Hafiz (College of Built Environment, 2023)
Mall walking is the phenomenon of people walking inside the mall when the mall is not in operational time.